A (Post-) Keynesian perspective on "financialisation" - Eckhard Hein (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2009)
Post-Keynesian demand driven distribution and growth models, based on the notion of distribution conflict between different groups, have been critical regarding the macroeconomic effects of 'financialisation'. In the present paper, firstly, we attempt to identify theoretically and empirically the main channels of influence of 'financialisation' on investment, saving and distribution in order to obtain a precise macroeconomic meaning of 'financialisation' in a distribution and growth context. Secondly, we analyse the effects of 'financialisation' in a simple stock-flow consistent Post-Keynesian/Post-Kaleckian distribution and growth model and we show that with 'normal' parameter constellations 'financialisation' generates systemic instability. – – Die makroökonomischen Effekte der "Finanzialisierung" sind mit Hilfe Nachfrage getriebener post-keynesianischer Verteilungs- und Wachstumsmodelle, die Verteilungskonflikte zwischen verscheidenen sozialen Gruppen berücksichtigen, kritisch diskutiert worden. In der vorliegenden Arbeit wird erstens versucht, die Einflusskanäle der "Finanzialisierung" auf Investitionen, Ersparnis und Verteilung theoretisch und empirisch zu identifizieren, um so eine präzise makroökonomische Bedeutung von "Finanzialisierung" in einem Verteilungs- und Wachstumskontext zu gewinnen. Zweitens werden dann die Effekte von "Finanzialisierung" in einem einfachen "stock-flow" konsistenten Verteilungs- und Wachstumsmodell analysiert und es wird gezeigt, dass die "Finanzialisierung" unter normalen Parameterkonstellationen eine systemische Instabilität hervorruft.
urn:nbn:de:101:1-20090713103
Keywords: 330; Finanzkapitalismus; Postkeynesianismus; Makroökonomik; Verteilungstheorie; Wachstumstheorie; Wirtschaftliche Instabilität; Theorie